Wpływ przewlekłego działania metali ciężkich na narząd wzroku - Mulak, Małgorzata; Misiuk-Hojło, Marta; Markuszewski, Bartłomiej; Dembska, Karolina (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of the study was to investigate relationship between chronic occupational exposure to heavy metals and eyesight, with particular lead influence. Material and methods: The experimental group was composed of 120 workers of Copper Steelwork Plant “Legnica”, divided into 2 groups, based on the degree and period of exposure to heavy metals. 75 men hired in direct production with work residency of 7 to 34 years (mean 21.2) made the experimental Group A – the occupationally exposed group. Group B with 45 white-collar men with work residency of 4 to 39 years (mean 19.8) made the environmentally exposed group. All workers underwent complex ophthalmic examination with particular lens investigation following pupil dilation, lead and cadmium level in full blood determination and free erythrocyte protoporphyrin (FEP) test, as indicator of human body lead overload. Results: Mean lead levels in both groups were considerably higher than permissible concentration in biological material (PCB) for occupationally exposed workers, and was higher for those working directly in production. Free erythrocyte protoporphyrin (FEP) level was correct in both groups. Lenticular changes were noticed in 26 (21.7%) patients, of whom 18 (69.2%) were hired in direct production. Similarly, fundus changes were shown in 17 patients, 16 (22%) from Group A; changes in field of vision in 3 patients. Furthermore, 15 men working in direct production complained of burning sensation, tearing and periodic redness in the eyes. Conclusions: Mean blood cadmium and lead levels, higher in occupationally exposed workers was statistically important only in case of lead. However, the correct FEP level indicates that an organism was not overload with lead. In these workers (group A) lenticular changes were observed more often and were more intense (cortex opacitates, posterior subcapsular cataract). Fundus changes noticed in both groups were of low degree and coexisting diseases may have promoted their progression. Field of vision changes noticed in 3 workers may have been caused by lead toxicity to optic nerve. Periodical conjuctival inflammatory states are caused by irritative dust and smoke therefore protective eye wear is indicated.